Metadata Analysis as a Criterion for Quality in e-Learning - Zbigniew Meger (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
Metadata describes learning objects LO and whole courses which are widely used in various e learning systems. Different specifications of metadata describe schemes, including Dublin Core (DC), IMS and Learning Object Metadata (LOM). They define fields that can be used for qualitative verification of described objects or courses. In this way it will be possible both quick evaluations of subjects included in courses and learning objects LO, as well as structure, accuracy, method of teaching or working. Proper metadata analysis allows the assessment of whole educational process, which is built on the basis of learning objects LO. This enables rapid evaluation of planned or already performed courses of distance learning.